The vegan cake bible : the definitive guide to baking, building and decorating spectacular vegan cakes - Kidd, Sara (Baker) (Smith Street Books, 2022)
"In this easy-to-follow book, author, pastry chef, and vegan cake queen Sara Kidd shares her vast knowledge of the science behind vegan baking and how to make foolproof creations every time. With step-by-step tutorials for frosting and decorating, mix and match ideas, and recipes for gluten-free cakes that actually work, Sara teaches you the ingredients, tools, and tips to master the art of vegan baking"--